Decreased Expression of GPER1 Gene and Protein in Goiter. (12th March 2015) - Weber, Raquel; Bertoni, Ana Paula Santin; Bessestil, Laura Walter; Brum, Ilma Simoni; Furlanetto, Tania Weber
Abstract : Goiter is more common in women, suggesting that estrogen could be involved in its physiopathology. The presence of classical estrogen receptors (ER α and ER β ) has been described in thyroid tissue, suggesting a direct effect of estrogen on the gland. A nonclassic estrogen receptor, the G-protein-coupled estrogen receptor (GPER1), has been described recently in several tissues. However, in goiter, the presence of this receptor has not been studied yet. We investigated GPER1 gene and protein expressions in normal thyroid and goiter using reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blot, respectively. In normal thyroid (n = 16 ) and goiter (n = 19 ), GPER1 gene was expressed in all samples, while GPER1 protein was expressed in all samples of normal thyroid (n = 15 ) but in only 72% of goiter samples (n = 13 ). When comparing GPER1 gene and protein levels in both conditions, gene expression and protein levels were higher in normal thyroid than in goiter, suggesting a role of this receptor in this condition. Further studies are needed to elucidate the role of GPER1 in normal thyroid and goiter.